Cryptococcus gattii meningoencephalitis in an HIV-negative patient from the Peruvian Andes Meningoencefalite causada por Cryptococcus gattii em um paciente HIV-negativo procedente dos Andes Peruanos - Ericson L. Gutierrez; Willi Valqui; Luis Vilchez; Lourdes Evangelista; Sarita Crispin; Mercedes Tello; Marcos Ñavincopa; Vilma Béjar; José Gonzáles; Alex G. Ortega-Loayza (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
We report a case of an immunocompetent Peruvian patient from the Andes with a one-month history of meningoencephalitis. Cryptococcus gattii was identified from a cerebrospinal fluid culture through assimilation of D-proline and D-tryptophan as the single nitrogen source. Initially, the patient received intravenous antifungal therapy with amphotericin B. The patient was discharged 29 days after hospitalization and continued with oral fluconazole treatment for ten weeks. During this period, the patient showed clinical improvement with slight right-side residual weakness. Through this case report, we confirm the existence of this microorganism as an infectious agent in Peru. Nós reportamos o caso de um paciente peruano immunocompetente proveniente dos Andes com história de um mês com meningoencefalite. Foi identificado o Cryptococcus gattii na cultura de liquido cerebrospinal através da assimilação de D-prolina e D-tryptofano como fonte única de nitrogênio. Inicialmente, o paciente recebeu tratamento antifúngico intravenoso com amfotericina B. O paciente foi liberado 29 dias depois da hospitalização, seguindo tratamento oral durante 10 semanas com fluconazol. Durante este período, o paciente apresentou melhoria clinica e uma leve fraqueza residual direita. Com o reporte do caso, nós confirmamos a existência desse microorganismo como agente infeccioso em nosso país.